Influence of active cooling on microstructure and mechanical properties of wire arc additively manufactured mild steel - Dash, Aruntapan; Squires, Lile; Avila, Jose D.; Bose, Susmita; Bandyopadhyay, Amit (Frontiers in Mechanical Engineering, 2023)
Additive manufacturing (AM) of metals attracted attention because it can produce complex structures in a single step without needing part-specific tooling. Recently, the wire arc additive manufacturing (WAAM) process gained popularity due to its low cost of operation, the feasibility of large-scale part fabrication, and ease of operation. This article represents the fabrication of cylindrical shape mild steel (ER70S-6) samples through a gas metal arc (MIG) - based hybrid WAAM system with and without an active cooling setup. The surface/volume defects can be seen on the cylindrical sample fabricated without an active cooling setup. Defect quantification and phase analysis are performed. The primary phase formed was α-iron in all samples. Microstructural analysis revealed nonuniform microstructures for samples fabricated without active cooling; however, samples with active cooling showed a uniform microstructure along the build direction. A decreasing trend in hardness from the first layer to the final layer has been observed in all cases. The variation in the properties can be attributed to their respective processing strategies.